Blockchain Depolyment in Energy Supply Chain Management: Implications for Report Integrity - Al-Madani, Mohammed; Fernando, Yudi; Pua, Wee Sin (Penerbit Universiti Malaysia Pahang, 2022)
This study aims to investigate literature findings on the current blockchain technology requirement. The obtained findings on blockchain technology requirements and limitations, helps to draw conclusions on the adoption of blockchain technology in energy consumption reporting. The blockchain technology offers transparency of energy consumption reports. Blockchain keeps all the transactional records and guarantees security, and decentralization between the blockchain network. Blockchain technology integration for energy consumption can promote transparency and integrity of energy management reporting. Among reasons for companies’ reluctance to report energy consumption is non-transparency, unnecessary cost for report, and lack of regulation to release an energy consumption report or it is voluntary in best cases. This paper reviewed 121 papers related to the topic and conclusions drawn based on findings of previous literature. Blockchain can help to alleviate the issues of transparency and cost related to energy reporting. Decision and policy makers should offer incentives and include regulations on energy reporting requirements. The reporting should be requested through blockchain network to guarantee transparency and integrity.